Pure tocotrienol concentrate protected rat gastric mucosa from acute stress-induced injury by a non-antioxidant mechanism - Rodzian, Mohd Nor Syidiq; Ibrahim, Ibrahim Abdel Aziz; Fahami, Nur Azlina Mohd; Ismail, Nafeeza Mohd (Polish Journal of Pathology, 2013)
Stress has been implicated as a risk factor of various major health problems, such as stress-induced gastric mucosal injury. This study was performed to investigate the action of a pure preparation of tocotrienol (T3) concentrate, made up of 90% -tocotrienol and 10% γ-tocotrienol, on gastric injury of rats induced by water-immersion restraint stress (WIRS). Fourteen male Sprague-Dawley rats (200-250 g) were divided into two equal groups: a control group and a treated group. The treatment group received T3 concentrate at 60 mg/kg body weight daily for 28 days. The body weights of rats were recorded daily before the treatment was given. At the end of the treatment period, all rats were subjected to WIRS for 3.5 hours, following which the rats were euthanized. The stomachs were isolated and opened along the greater curvature for the examination of lesions and measurements of gastric malondialdehyde (MDA) and prostaglandin E 2 (PGE 2 ) contents. The mean gastric mucosal lesion index in the treated rats was significantly lower than that in the control rats. This suggests that the T3 concentrate has the ability to confer protection to the gastric mucosa against gastric injury induced by acute stress. No significant difference was observed for changes in body weight before and after the treatment. The gastric PGE 2 content in both groups was comparable. However, the gastric MDA content was significantly higher in the treated group compared to the control group, indicating that the T3 supplementation was not able to reduce the lipid peroxidation process. This study concludes that the T3 concentrate has the ability to protect the gastric mucosa from stress-induced injury by a non-antioxidant mechanism.